Rethinking the Final Frontier: Cosmo-Logics and an Ethic of Interstellar Flourishing. Issue 1 (2nd January 2017) - Kearnes, Matthew; van Dooren, Thom
Abstract : In recent years a range of corporate and governmental entities have made increasingly strident moves toward the establishment of an off-Earth mining industry, often touting an imminent "gold rush in space." For many proponents these proposals are thoroughly entangled with an even more ambitious set of possibilities for a new age of human history in space that will include the exploration and eventual colonization of extraterrestrial environments. This article takes off-Earth mining as an entry point into this complex terrain, exploring the way in which problematically homogenous notions of humanity and an open and available space are being deployed to do a kind of regulatory ethical work that simultaneously imposes and overcomes any limits to off-Earth expansion. In contrast to such an approach, this article aims to develop an ethics of interstellar flourishing grounded in an attentiveness to the consequential processes of worlding that are already linking up and remaking possibilities for everyone, both on and off-world.